Customary Law for Equitable Spatial Planning: Preventing Social Bankruptcy and Enhancing Community Welfare - Adnan, Muhammad Ali; Sunarto, Atika; Khair, Azizan (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study examines the role of customary law as an instrument for equitable spatial planning in preventing socio-economic bankruptcy and enhancing the welfare of indigenous communities in Indonesia. As a living and dynamic legal system, customary law embodies values of ecological balance, deliberation, and restrictions on land conversion without community consent. However, in practice, many regional spatial planning policies have failed to integrate customary norms, resulting in spatial conflicts and social disintegration.Purposes of the Research: The research aims to analyze how customary law can serve as both a normative and practical foundation for equitable spatial planning, and how integrating local values can prevent social bankruptcy while strengthening the welfare of indigenous peoples.Methods of the Research: This study employs a normative-juridical approach combined with socio-legal analysis to examine the interaction between statutory law and customary practices in spatial management, supported by case studies of customary land conflicts in Salang Tungir Village (Deli Serdang Regency) and Aras Napal Village (Langkat Regency).Results of the Research: Findings indicate that neglecting customary law norms in spatial planning leads to the loss of community access to productive spaces, weakens local economies, and triggers social conflicts. Conversely, applying customary law in spatial planning—through recognition of customary rights, consent mechanisms, and active community participation—fosters spatial justice and enhances community welfare. This study introduces the concept of “customary law-based spatial planning,” which integrates local values with principles of social and ecological justice in national spatial planning policies, offering a framework for more inclusive and sustainable development.